(untitled) (KYAMC Journal, 2022)
Background: Although the global number of newborn deaths declined from 5 million (1990) to 2.4 million (2020), children face the greatest risk of death within their first 28 days of life. Dhaka Medical College Hospital (DMCH) is the biggest tertiary hospital in Bangladesh serving all incoming patients free of cost. Objectives: We studied here the clinical patterns and outcomes of neonatal surgeries in DMCH from July 2014 to June 2016. Materials and Methods: This prospective descriptive study included 500 neonates with surgical problems who had attended from July 2014 to June 2016. Data were collected at admission and thereafter by predesigned data collection sheet. Results: Male female ratio was 1.5: 1. Majority of the neonates (346) presented during the first week of life (69.2%). Presented within 1 hour to 28 days (mean 7.1 days ± SD 8.8), weighing 1.5 - 5.0 kilogram (mean 2.6 in kg ± SD 0.5). Surgical indications in order of sequences were Neonatal Intestinal Obstruction (NIO), gastroschisis, omphalocele, abscess/cellulitis, hydronephrosis, congenital diaphragmatic hernia, Tracheo esophageal atresia or fistula (TEF), bladder exstrophy, malignancy, Infantile Hypertrophic Pyloric Stenosis (IHPS), cloacal exstrophy, neonatal injury, patent urachus, prune belly syndrome, amniotic band syndrome. NIO was in the form of Anorectal Malformations (ARM), Hirschsprung disease, septicemia, intestinal atresia, meconium ileus, volvulus neonatorum, multiple congenital anomalies, obstructed inguinal hernia. Total 384 patients were managed surgically. 125 (25.0%). 33 (6.6%) died preoperatively and 92 (18.4%) died postoperatively. Conclusion: Early diagnosis, resuscitation, skilled staff, ICU facilities etc. are crucial for the best outcomes of neonatal surgical problems. KYAMC Journal Vol. 13, No. 02, July 2022: 86-93